Improvement of the method of scenario analysis of functional requirements to an information system - Mohammed, Mohammed Q.; Muhamed, Saif Q.; Ievlanov, Maksym; Gazetdinova, Zarina (Eastern-European Journal of Enterprise Technologies, 2019)
We have considered a task on improving the base method for scenario analysis of the functional requirements to an information system (IS). The results from studies of the methods for scenario analysis of the functional requirements to IS have been analyzed. Their main drawback in our opinion is the need for the implementation of these methods by analysts manually only. To overcome this shortcoming, it has been proposed to improve the base method for scenario analysis by using the models and methods based on a formal knowledge representation. For a formal description of the representation of a scenario for implementing a functional requirement at the level of knowledge, it has been proposed to use a model of structural patterns in the design of functional requirements. It has been shown that the formal description of knowledge derived from the Use Case diagrams is a special case of a given model. We have proposed a model of the subclass of structural patterns for designing scenarios for the implementation of functional requirements. An improved method of scenario analysis of functional requirements to IS has been constructed. The essence of improvement is the selection from the publications of scenarios for meeting the requirements of knowledge and a subsequent analysis of knowledge-oriented descriptions of these scenarios in order to identify overlapping scenarios for the implementation of various functional requirements to IS. To identify and address the cases of such duplication, it has been proposed to use the improved method of synthesis of architecture descriptions variants for a created IS. An example is provided of testing the improved method of scenario analysis of functional requirements in the course of analysis of functional requirements to a project of the functional module of labor safety. The verification results confirm reliability of the proposed method. The proposed improved method for scenario analysis of functional requirements to IS makes it possible to obtain a description of the architecture of a created IS based on a much smaller amount of information on the functional requirements to IS.